Descripción anestesiológica del efecto de un protocolo en base a Azaperona y Ketamina en conejo doméstico (oryctolagus cuniculus) - Flores, Estefanía; Caroca, Paulina; Cattaneo, Gino; Bastías, Andrés; Morales, Angélica (Avances en Ciencias Veterinarias, 2007)
The effects of the anaesthetic protocol, based on a premedication with atropine and azaperone (Stresnil ®) and the anesthetic induction with a 0.5% ketamine solution, were studied in 25 healthy adults rabbits. Each animal was premed with 0.04 mg/kg b.w. atropine, and 1.5 mg/kg azaperone to provide relaxation and decrease the muscle hyper-tonus produced by the dissociative anesthetic. After each drug administration, the physiologic parameter measure was registered. The ketamine induction was done with a 0.5% ketamine solution, and the induction was determined by the lost of both, the straight head and the righting reflex. The heart rate, respiratory rate and arterial blood pressure were determined and registered every 5 minutes, the body temperature was controlled every 15 minutes, every measurement was done until the moment of recovery of the both previously mentioned reflex. The average dose of ketamine injected to achieve the induction anesthetic state, the time it takes the administration of that ketamine dose, the resultant surgical anesthetic period in minutes, and the post anesthetic motor depression time, were also determined and recorded. The average I.V. dose induction of 0,5% ketamine solution was 4.49 mg/kg of body weigh, injected in a average time of 9.56 seconds, providing a surgical anesthetic period of 10.64 minutes followed by a post anesthetic motor depression period of 5.64 minutes. Under the effects of the anesthetics drugs association conforming this protocol, almost all physiological parameters remains in the normal ranges described for the specie, only the arterial blood pressure exhibited an average value under the normal value given for rabbits in the literature.